Cardiorespiratory responses to low-level ozone exposure: The inDoor Ozone Study in childrEn (DOSE). (October 2019) - Huang, Jing; Song, Yi; Chu, Mengtian; Dong, Wei; Miller, Mark R.; Loh, Miranda; Xu, Junhui; Yang, Di; Chi, Rui; Yang, Xuan; Wu, Shaowei; Guo, Xinbiao; et al.
Abstract: Background: Indoor air pollution has emerged as a significant environmental and public health concern in recent years. However, evidence regarding the cardiorespiratory effects of indoor ozone is limited, and the underlying biological mechanisms are unclear, especially in children. Our study aimed to assess the cardiorespiratory responses to indoor ozone exposure in children. Methods: A repeated-measure study was conducted in 46 middle-school children in Beijing, China. Real-time concentrations of ozone, along with co-pollutants including particulate matter (PM) and black carbon (BC), were monitored in classrooms from Monday to Friday. Three repeated health measurements of cardiorespiratory functions, including ambulatory electrocardiogram (ECG), blood pressure, fractional exhaled nitric oxide (FeNO) and lung function, were performed on each participant. Mixed-effect models were used to evaluate the effects of indoor ozone exposure. Results: The mean (SD) indoor ozone concentration was 8.7 (6.6) ppb during the study period, which was largely below the current guideline and standards. However, even this low-level ozone exposure was associated with reduced cardiac autonomic function and increased heart rate (HR) in children. For instance, per interquartile range (IQR) increase in ozone at 2-hour moving average was associated with −7.8% (95% CI: −9.9%, −5.6%) reduction in standard deviation of all normal-to-normal intervals (SDNN), and 2.6% (95% CI: 1.6%, 3.6%) increment in HR. In addition, the associations were stronger at high BC levels (BC ≥ 3.7 μg/m 3 ). No significant associations were found for airway inflammation and pulmonary function. Conclusions: Exposure to low-level indoor ozone that is not associated with respiratory effects was significantly related to disturbed cardiac autonomic function and increased HR in children, which suggested a possible mechanism through which ozone may affect cardiovascular health in children, and indicated more protective measures should be taken to alleviate the acute adverse effects of indoor ozone in this susceptible population. Graphical abstract: Unlabelled Image Highlights: The cardiorespiratory responses to indoor ozone exposure in children were explored. Indoor ozone <10 ppb was associated with cardiovascular responses in children. The cardiovascular responses were stronger at high black carbon levels. Respiratory effects were not found at indoor ozone <10 ppb in children.